2010
DOI: 10.1590/s1678-58782010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study on workpiece temperature when tapping hardened AISI H13 using different cooling systems

Abstract: Tapping operations on hardened steels have always been a great challenge. Dry machining and two cooling systems were used when tapping hardened AISI H13 (53 HRC). Embedded thermocouples were used for temperature measurement close to the thread diameter in the radial and axial direction. A FEA model was used to evaluate the heat "Q", and coefficient of convection "h". The lowest temperature peak occurred with the flooded system, followed by the MQL, and dry condition. The heat and coefficient of convection inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…In their experimental tests, the efficiency in reducing these forces could be noted when the cutting fluid was used. Brandão and Coelho 21 studied threading with the removal of material applied to AISI H13 hardened steel with different lubrication systems and showed that there is a significant temperature increase if cutting speed is increased also. The temperature was monitored with the use of thermocouples inserted in the specimens, which obtained measurements of the heat generation created by the process and the cooling rate of the systems used in it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their experimental tests, the efficiency in reducing these forces could be noted when the cutting fluid was used. Brandão and Coelho 21 studied threading with the removal of material applied to AISI H13 hardened steel with different lubrication systems and showed that there is a significant temperature increase if cutting speed is increased also. The temperature was monitored with the use of thermocouples inserted in the specimens, which obtained measurements of the heat generation created by the process and the cooling rate of the systems used in it.…”
Section: Discussionmentioning
confidence: 99%
“…Brandão et al. 21 studied the heat flux in the machine tapping of hardened steels. The authors monitored the temperature through embedded thermocouples in the workpieces, and the results obtained by the authors demonstrate that the temperature in the tapping process increases proportionally with the increase of cutting speed.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of various tap design parameters and tapping conditions on the formation of split crests were investigated to arrive at an optimal tap design. In addition to these studies, studies such as high-accuracy classi cation of thread quality in tapping processes [15], fatigue analysis of threaded connections using the local strain approach [16], use of the coolant [17] are available in the literature. In addition, nite element analysis and cutting zone temperatures are also among the subjects investigated [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The second method that can diminish the amount of cutting fluid in the machining process is the use of minimum quantities of lubricant. Brandão et al [13] show that the effects of heat can be minimized with the use of cooling with a minimum quantity of lubricant. The finite element analysis shows that this system has the same ability to remove heat from the machining process with a smaller amount of cutting fluid.…”
Section: Introductionmentioning
confidence: 99%